(untitled) (Dhaka University Journal of Science, 2018)
Several metal complexes of pantoprazole, [Cu(PPZ)(H2O)Cl], [Zn(PPZ)2], [Cd(PPZ)2].1.5H2O and [Hg(PPZ)(H2O)Cl] have been synthesized and characterized. Elemental analysis, IR, UV-Visible spectral analysis, magnetic measurement, thermogravimetric analysis, differential scanning calorimetric and cyclic voltammetric techniques were used for their characterization. The lipophilic weak base pantoprazole (PPZ) act as a potential bidentate ligand forming coordination complexes with divalent metal ions through anionic imidazolyl N- and O atom of sulfinyl >S=O group. All complexes possess tetrahedral geometry. Dhaka Univ. J. Sci. 66(2): 151-156, 2018 (July)